Anticancer activities of parthenolide in primary effusion lymphoma preclinical models. Issue 8 (8th June 2021) - Karam, Louna; Abou Staiteieh, Soumaiah; Chaaban, Rady; Hayar, Berthe; Ismail, Bassel; Neipel, Frank; Darwiche, Nadine; Abou Merhi, Raghida
Abstract: The sesquiterpene lactone parthenolide is a major component of the feverfew medicinal plant, Tanacetum parthenium . Parthenolide has been extensively studied for its anti‐inflammatory and anticancer properties in several tumor models. Parthenolide's antitumor activities depend on several mechanisms but it is mainly known as an inhibitor of the nuclear factor‐κB (NF‐κB) pathway. This pathway is constitutively activated and induces cell survival in primary effusion lymphoma (PEL), a rare aggressive AIDS‐related lymphoproliferative disorder that is commonly caused by the human herpesvirus 8 (HHV‐8) infection. The aim of this study is to evaluate the targeted effect of Parthenolide both in vitro and in vivo. Herein, parthenolide significantly inhibited cell growth, induced G0 /G1 cell cycle arrest, and induced massive apoptosis in PEL cells and ascites. In addition, parthenolide inhibited the NF‐ĸB pathway suppressing IĸB phosphorylation and p65 nuclear translocation. It also reduced the expression of the DNA methylase inhibitor (DNMT1). Parthenolide induced HHV‐8 lytic gene expression without inhibiting latent viral gene expression. Importantly, DMAPT, the more soluble parthenolide prodrug, promoted delay in ascites development and prolonged the survival of PEL xenograft mice. This study supports the therapeutic use of parthenolide in PEL and encourages its further clinical development.